Defining and Measuring Workforce Development in the United States in a Post-Bipartisan Era - Brian Holland (Global Labor Organization (GLO), 2018)
The bipartisan acceptance of a federal role in workforce development policy is no longer in play as a result of ideological differences in the definition of workforce development which arise from a lack of coherent and misunderstood outcomes. My attempt here is to posit a new definition for workforce development that explains what these activities actually are and to raise three criteria for outcome metrics that can be used to evaluate the success of workforce investment under this new definition. By suggesting the process of workforce development and by proposing metric criteria which we can use to measure progress, I believe that a new bipartisan consensus can re-emerge, while recognizing the limitations of federal public expenditure. This consensus can, then, be used to generate a more appreciative role of active labor market policy at the national level using a process-evaluation model.
Keywords: J68; J24; I38; I32; 330; Workforce development; employability; public policy; outcomes framework; process-evaluation